(untitled) (The Journal of Theoretical Accounting Research, 2026)
The globalization of trade has significantly reshaped the economic trajectories of emerging market economies (EMEs), offering new avenues for growth while simultaneously exposing financial vulnerabilities. The study explores the financial consequences of global trade policies on EMEs through a comprehensive assessment of trade openness, foreign direct investment (FDI), and financial development indicators. Employing a mixed-methods research design, the study analyzed cross-country data from 2000 to 2024 for five strategically selected EMEs: India, Indonesia, Vietnam, Nigeria, and South Africa. Quantitative analysis included correlation matrices and regression models, while qualitative insights were derived from institutional and policy documents, enabling a multi-dimensional interpretation of trade-finance linkages. The results revealed a robust positive correlation between trade openness and both FDI inflows and private credit growth, suggesting that EMEs with higher degrees of global integration tend to exhibit stronger financial systems. Vietnam emerged as a leading case, with high global value chain (GVC) participation and sustained financial development, while Nigeria’s performance underscored the role of weak institutions in constraining the benefits of trade. The study concludes that trade liberalization must be complemented by domestic financial reforms and institutional strengthening to translate global integration into inclusive financial progress. Policymakers are advised to foster synchronized strategies that integrate trade policy with financial sector development, emphasizing GVC participation, digital innovation, and sustainability. Future research should consider firm-level and subnational analyses to better understand the microeconomic dynamics of trade and finance.